Kasus Covid-19 Tahun 2021 di Kalimantan Ditinjau dari Sektor Pertanian dan Pertambangan - 'Afifah, Nazihah (JIEP: Jurnal Ilmu Ekonomi dan Pembangunan, 2024)
The research aims to determine the Covid 19 Case of 2021 in Kalimantan in terms of the agricultural and mining sectors. This type of quantitative research using multiple linear regression analysis with the OLS method. The results showed that GRDP per capita, total population, share of the agricultural sector, and share of the mining sector had a significant effect on Model I indicating that the agricultural and mining sectors had a lower risk of confirmed cases of the cumulative number of positive cases of Covid-19, while the population and per capita GDP had a higher greater risk in the spread of covid 19 cases, Model II, showing that the agricultural and mining sectors have a lower risk of spreading the cumulative number of covid-19 death cases and Model III, showing the cumulative case of covid 19 deaths has an effect and is higher on the cumulative number of positive cumulative cases of covid -19.